2006
DOI: 10.1177/070674370605100703
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapies in the Management of Obsessive—Compulsive Disorder

Abstract: T he first reports of the potential for medications to exert an antiobsessional effect in patients without major depression were published about 35 years ago (1-4). The tricyclic antidepressant G-34586, or CMI, was used successfully in these first attempts. The serendipitous finding of its beneficial effect on obsessions in depression patients motivated its use in that disorder. Several case series in the following decade seemed to confirm the usefulness of this medication in treating OCD, then denoted obsessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 121 publications
1
18
0
1
Order By: Relevance
“…In contrast, the prefrontal cortex (PFC), thought to be the main target in the treatment of OCD, does not undergo desensitization for up to 8 weeks ( 276 ). In addition, animal studies have indicated that higher concentrations of SSRIs are needed to achieve desensitization in the PFC than in the hypothalamus and hippocampus ( 277 ). These observations are congruent with clinical experience that longer medication trials and higher doses of medications are needed to achieve therapeutic benefi t in the treatment of OCD than those needed in the treatment of depression.…”
Section: Pharmacological Treatmentsupporting
confidence: 55%
“…In contrast, the prefrontal cortex (PFC), thought to be the main target in the treatment of OCD, does not undergo desensitization for up to 8 weeks ( 276 ). In addition, animal studies have indicated that higher concentrations of SSRIs are needed to achieve desensitization in the PFC than in the hypothalamus and hippocampus ( 277 ). These observations are congruent with clinical experience that longer medication trials and higher doses of medications are needed to achieve therapeutic benefi t in the treatment of OCD than those needed in the treatment of depression.…”
Section: Pharmacological Treatmentsupporting
confidence: 55%
“…Nevertheless, anatomical hypotheses derived from neuroimaging (Dougherty et al, 2004), clinical pharmacology of OCD, and basic neuropharmacology of the implicated circuitry (Blier et al, 2006;Greenberg et al, 1997;Westenberg et al, 2007) provide some key starting points. As already discussed, human neuroimaging data suggest that abnormalities in OFC/ACC-basal ganglia-thalamic circuitry are central to the pathophysiology of OCD and responses to treatment.…”
Section: Integrating Anatomical and Neurochemical Modelsmentioning
confidence: 99%
“…Yet, E/RP does not help all individuals, and those who benefit, often remain symptomatic upon treatment completion. Alternative interventions, such as serotonergic medications, have modest efficacy and are often accompanied by undesirable side effects (Blier et al, 2006;Denys, 2006). Given this, further investigation into approaches that may enhance the therapeutic efficacy of E/RP is warranted.…”
Section: Introductionmentioning
confidence: 99%